Introducing the genetic improvement of olive trees in Morocco by crossbreeding - A, EL Oualkadi; B, Hajjaj; A, El Hereich; My H, Sedra (International Journal of Environment, Agriculture and Biotechnology, 2019)
The genetic improvement of the olive tree by crossing is a new work in Morocco and even in the olive countries of the Mediterranean. The objective of this work is to improve the performance of our selected Moroccan variety (Haouzia) by crossbreeding with European variety (Frontoio) with high-performance traits relating to the quality, quantity of fruit, oil and resistance to verticilliose. The result show Rate of fruit set is 63% as well as the fruiting rate of 50%.